Management of Knee Osteoarthritis in the Younger, Active Patient An Evidence-Based Practical Guide for Clinicians - Parker, David (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book is a rich source of practical guidance on the management of relatively young patients with osteoarthritis of the knee that will assist physicians and allied health professionals in enabling patients to remain active and sustain their quality of life. It provides up-to-date knowledge on the available treatment options, describes the evidence base for each option, and identifies the appropriate timing and indications. The book opens by considering the basic science behind osteoarthritis, which is critical to management. The many nonsurgical treatment modalities are then discussed, with particular focus on the importance of a multidisciplinary approach. Subsequent chapters address the role of surgical management, covering both techniques that attempt to preserve and possibly restore the native knee joint, such as meniscal and chondral surgery, arthroscopic debridement, and osteotomy for realignment of the joint, and those that involve joint replacement. The arthroplasty component of the text encompasses all areas of prosthetic resurfacing, including localized resurfacing, unicompartmental replacement, and total knee replacement. The book has been produced in cooperation with ISAKOS and the authors constitute an international faculty who provide a truly global perspective on the subject.